Associations between anemia and insomnia or excessive daytime sleepiness in older adults. Issue 3 (4th May 2023) - Kara, Osman; Elibol, Tayfun; Koc Okudur, Saadet; Smith, Lee; Soysal, Pinar
ABSTRACT: Objective: Sleep disorders including excessive daytime sleepiness (EDS), insomnia and anemia are both common. The aim of this study is to investigate associations between anemia and insomnia/EDS in the elderly. Methods: A total of 744 older outpatients were included in this cross-sectional study. Anemia was defined as a hemoglobin concentration below 12 g/dL in females and <13 g/dl in males. Patients were divided into two groups as anemic and non-anemic. The Epworth Sleepiness Scale score of ≥11 points indicates EDS. Insomnia Severity Index with scores of ≥8 indicates insomnia. Results: The mean age was 79.8±7.7 years. The prevalence of insomnia, EDS and anemia was 62.1%, 23.8%, and 47.2%, respectively. Insomnia (66.3% vs 58.5%) and EDS (29.6% vs 18.6%) were more common in patients with anemia compared to those without anemia (p<0.05). In univariate analysis, there were significant associations between anemia and insomnia [odds ratio (OR):1.4, 95% confidence interval (CI):1.0–1.9], and EDS (OR:1.8, 95% CI:1.3–2.6). In multivariate analysis, the relationship between insomnia and nocturia, chronic obstructive pulmonary disease (COPD), and number of drugs used persisted, whereas being male, of an older age, coronary arterial disease, COPD, Parkinson's disease, dementia, and urinary incontinence were associated with EDS (p<0.05), but there was no significant relationships between anemia and insomnia/EDS (p>0.05). Conclusion: The present data suggests that an elderly who has anemia is 1.4 times more likely to experience insomnia and 1.8 times more likely to experience EDS than those without anemia.